2011
DOI: 10.1007/s11136-011-0030-5
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Swedish translation of the general self-efficacy scale

Abstract: Across three cohorts, additionally stratified by gender, the S-GSE comprised one single latent factor and showed high internal consistency. However, since S-GSE was more strongly related to self-assessments of mental work capacity than physical work capacity regardless of sick-leave status, the S-GSE may not be a strong predictor of beliefs about physical work capacity across all populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
122
3
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(144 citation statements)
references
References 6 publications
15
122
3
4
Order By: Relevance
“…The respondents are asked to rate each item on a 4-point scale (1 = not at all true, 2 = barely true, 3 = moderately true, 4 = exactly true) and ratings are summed to a total score ranging from 10–40, where higher scores indicate higher levels of general self-efficacy. A validated Swedish version of the GSE scale [32] was used in this study. In a previous study, an increase of ≥ 5 points in the GSE scale was considered a threshold for minimal clinically important change [12].…”
Section: Methodsmentioning
confidence: 99%
“…The respondents are asked to rate each item on a 4-point scale (1 = not at all true, 2 = barely true, 3 = moderately true, 4 = exactly true) and ratings are summed to a total score ranging from 10–40, where higher scores indicate higher levels of general self-efficacy. A validated Swedish version of the GSE scale [32] was used in this study. In a previous study, an increase of ≥ 5 points in the GSE scale was considered a threshold for minimal clinically important change [12].…”
Section: Methodsmentioning
confidence: 99%
“…The mean item scores found in the present study were 2.4 and 1.9 for native Swedish women and foreign-born women, respectively. This may be compared with scores in a Swedish general population, who reported mean item scores of 2.9, and two sick-listed populations, who reported a mean item score of 2.9 and 2.8, respectively (Löve et al, 2012).…”
Section: Self-efficacymentioning
confidence: 99%
“…For example: "I can always manage to solve difficult problems if I try hard enough". The General Self-efficacy Scale has a reported Cronbach's α between .75 and .94 (Löve, Moore, & Hensing, 2012). In this study, the Cronbach's α was found to be acceptable at .68.…”
Section: The Measuresmentioning
confidence: 57%